Creating Incentives to Work in Ghana : Results from a Qualitative Health Worker Study - Lievens, Tomas (World Bank, Washington, DC, 2013)
The Ministry of Health, Ghana, is engaged in developing new Human Resources for Health (HRH) Strategy (2001-15); one that tries to draw on some of the evidence pertaining to the dynamics of the health labor market. This study is one of several efforts by the World Bank to support the Ministry of Health in its endeavor to develop a new evidence based HRH strategy. Using qualitative research (focus group discussions), this study carries out a microeconomic labor analysis of health worker career choice and of job behavior. The study shows how common problems related to distribution or performance of HRH are driven by the behavior of health workers themselves and are determined largely by select monetary and nonmonetary compensation. Such findings generate insights that provide a starting point for further analysis and a basis for the development of effective human resources for health policies.